OPTIMASI PEMBANGUNAN RUMAH BERDASARKAN TYPE DAN LUAS LAHAN UNTUK MENDAPATKAN LABA MAKSIMUM DENGAN MENGGUNAKAN PROGRAM THE MANAGEMENT SCIENTIST - Sarya, Gede (Universitas 17 Agustus 1945 Surabaya, 2013)
Graha residential development located on the Enchantment of the District Nirmala Kubutambahan BaliBuleleng Singaraja which is a strategic location because there will be a new addition to international airportNgurah Rai International Airport in the isthmus ( narrow strip of land ) between Denpasar and Nusa Dua area, inBadung regency, south Bali, which is already too crowded and no longer adequate for a drastic increase in thenumber of flight frequency , flight service users , and cargo . The purpose of this study was to perform simulationsbased on a comparison of the type of house construction in accordance with government regulations . Anddetermine the optimal profit housing by type and area of land . The data used in this study , namely primary andsecondary data related to land use, type of house and land area of each type , construction of public facilities andinfrastructure and the cost of production of each unit or type with linear programming techniques to thecalculation of The Management Scientist . Results, the calculations were performed with the program TheManagement Scientist using a ratio 0 : 6 : 0 : 3 : 1 obtain the most optimal results earnings by the number ofhousing units is as follows : = 0 Unit Type 36 , Type 45 = 204 739 units , rounded to 205 units , Unit Type 54 = 0 ,Type 70 = 102 370 units , rounded to 102 Units , Type 120 = 34 123 units , rounded to 34 units . Of the number ofhouses in point 1 above, the maximum total profit obtained is Rp 30,257,500,000.00 . A review of the researchsuggested above type of house can be developed further , not attached to the type that has been studied is type36 , 45 , 54 , and 70 , 120 meaning that in addition to the above type , other types are also investigated andhousing developer GRAHA CHARM NIRMALA need to consider the construction of a house by a comparativeanalysis - 1 with the composition of 1 : 5 : 1 : 2 : 1untuk meet the needs of its customers .Keywords : Optimization of housing , type and area of land .